The Role of Sibolangit Nature Tourism Park in Climate Change Mitigation: Aboveground Biomass, Carbon Stock, and CO2 Equivalent - Mariah Ulfa; Moehar Maraghiy Harahap; Yusran E Ritonga; Astri Winda Siregar; Pandu Yudha Adi Putra Wirabuana; Ida Mallia Ginting (Jurnal Sylva Lestari, 2026)
Carbon dioxide (CO2) is the main greenhouse gas, and its atmospheric concentration continues to increase. Globally, in 2019, the average CO2 at Earth’s surface reached 409.8 ppm. Information on carbon storage remains a strategic issue for sustainable forest management and climate change mitigation. Sibolangit Nature Tourism Park is a 24.85 ha conservation area with high biodiversity and a range of potential environmental services. This study aims to quantify the aboveground biomass, carbon stock, and CO2-equivalent emissions in the Sibolangit Nature Tourism Park. The study used 5% intensity sampling, resulting in 31 plots selected using simple random sampling. The plot size was 400 m2 (trees), 100 m2 (poles), 25 m2 (saplings), and 4 m2 (seedlings). The vegetation species, height and diameter at breast height were recorded to measure the biomass of trees, poles, and saplings. The aboveground biomass of vegetation was estimated using a non-destructive method with Chave’s allometric equation, while the biomass of seedlings was calculated using a destructive method according to SNI 7724-2019. The carbon stock was measured by multiplying the biomass by 0.47. The carbon stock value was then converted to CO2-equivalent using a conversion factor of 3.67. The results showed that Sibolangit Nature Tourism Park had an aboveground biomass of 525.73 t/ha, a carbon stock of 247.09 t C/ha, and a total carbon stock of 6140.30 t C, equivalent to 906.84 t CO2/ha. The study site had potential as an atmospheric CO2 absorber, indicating its primary role in climate change mitigation and in the FoLU Net Sink 2030 program. Keywords: allometric equation, conservation area, global warming, Sibolangit Nature Tourism Park, tropical forest